2015
DOI: 10.1186/s13071-014-0628-x
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne pathogens and the vector potential of ticks in China

Abstract: Ticks, as obligate blood-sucking ectoparasites, attack a broad range of vertebrates and transmit a great diversity of pathogenic microorganisms. They are considered second only to mosquitoes as vectors of human disease, and the most important vector of pathogens of domestic and wild animals. Of the 117 described species in the Chinese tick fauna, 60 are known to transmit one or more diseases: 36 species isolated within China and 24 species isolated outside China. Moreover, 38 of these species carry multiple pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
90
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 67 publications
0
90
2
Order By: Relevance
“…China has a relatively high tick species diversity, and over 120 species (about 13% of world species) have been described across its geography and infesting different hosts (Bush & Robbins, ; Chao, Hsieh, & Shih, ; Chao, Lu, Lin, & Shih, ; Z. Chen et al, ; Deng & Jiang, ; Duan, ; T. Guo, Sun, Xu, & Durden, ; Y. Guo, Sun, & Xu, ; W. Li, Sun, Zhang, & Xu, ; Wen & Chen, ; Yin & Luo, ; X. Yu, Ye, & Gong, ). Owing to the medical and economic importance of ticks, increasing studies have paid more attention to tick biology (Z. Chen, Yu, Yang, Zheng, & Liu, ; J. Li et al, ; J. Liu, Liu, Zhang, Yang, & Gao, ; Ma et al, ), tick ecology (T. Wang et al, ; Zheng, Yu, Zhou, Yang, & Liu, ), and tick‐borne disease (Chu et al, ; Fang et al, ; Wu, Na, Wei, Zhu, & Peng, ; Z. Yu et al, ), especially reports of the new emergence of tick‐borne pathogens in recent years (H. Li et al, ; Y. Z. Zhang & Xu, ).…”
Section: Introductionmentioning
confidence: 99%
“…China has a relatively high tick species diversity, and over 120 species (about 13% of world species) have been described across its geography and infesting different hosts (Bush & Robbins, ; Chao, Hsieh, & Shih, ; Chao, Lu, Lin, & Shih, ; Z. Chen et al, ; Deng & Jiang, ; Duan, ; T. Guo, Sun, Xu, & Durden, ; Y. Guo, Sun, & Xu, ; W. Li, Sun, Zhang, & Xu, ; Wen & Chen, ; Yin & Luo, ; X. Yu, Ye, & Gong, ). Owing to the medical and economic importance of ticks, increasing studies have paid more attention to tick biology (Z. Chen, Yu, Yang, Zheng, & Liu, ; J. Li et al, ; J. Liu, Liu, Zhang, Yang, & Gao, ; Ma et al, ), tick ecology (T. Wang et al, ; Zheng, Yu, Zhou, Yang, & Liu, ), and tick‐borne disease (Chu et al, ; Fang et al, ; Wu, Na, Wei, Zhu, & Peng, ; Z. Yu et al, ), especially reports of the new emergence of tick‐borne pathogens in recent years (H. Li et al, ; Y. Z. Zhang & Xu, ).…”
Section: Introductionmentioning
confidence: 99%
“…It mainly infests birds and occasionally can also bite humans (Uchikawa, ). Although a case of human dermatitis was recorded in 1986 after a bite by A. japonicus , no pathogen has been identified from this tick species in China (Yu et al , ; Li et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…They are grouped into three families: the Ixodidae (hard ticks), Argasidae (soft ticks) and Nuttalliellidae, with more than 900 tick species being reported to date (Dantas-Torres et al, 2012). Among them, approximately 200 species have been described in the family Argasidae globally (Guglielmone et al, 2010) and 13 species were found within China, with eight of the latter species being confirmed as causing host illnesses (Chen et al, 2010;Yu et al, 2015). The tick Argas japonicus Yamaguti, Clifford and Tipton, 1968 is mainly distributed in Japan, Korea (Uchikawa & Sato, 1969) and China (Teng, 1983) and usually has two to four nymphal instars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PCR-RLB was used for rapid, simultaneous detection and differentiation of numerous species of Babesia and Theileria even in mixed infection (Schnittger et al, 2004;Niu et al, 2009;Iqbal et al, 2013). Although there have been several studies of the frequency of ixodid tick species and the prevalence of tick-borne diseases in most areas in China (Chen et al, 2014a;Li et al, 2014a;Liu et al, 2015;Yu et al, 2015), little information is available about the prevalence of pathogens in ticks. Thus, the investigations of known parasites and new tick-piroplasms associations are important and significant for the animal health and livestock industry.…”
mentioning
confidence: 99%